Rethinking Post-secondary Access and Engagement for Low-income Adult Learners Through a Community Hub Partnership Approach - Bourke, Alan; Tascón, Clara; Vanderveken, James; Ecker, Emily (The Canadian Journal for the Study of Adult Education / La revue canadienne pour l’étude de l’éducation des adultes)

(untitled) (Canadian Association for the Study of Adult Education / L’Association canadienne pour l’étude de l’éducation des adultes, 2022)
This paper draws upon a case study of a campus-community partnership program in Ontario that delivers tuition-free college courses to low-income adult learners in community hub locations. By co-locating college classrooms in existing neighbourhood gathering places (i.e., a community centre and a public library), our research explores whether integrating college capacity and resources in community hub locations can help increase the accessibility of post-secondary education. In doing so, we address a gap in the research in exploring how community hubs provide a support structure that can help boost the motivation of low-income adult learners and better facilitate their pathway to a post-secondary education. Drawing upon a thematic analysis of interview data, we (a) analyze partners’ perspectives on the community hub–based approach in bolstering the accessibility of higher education, (b) reflect on the process of campus-community engagement underpinning the partnership structure, and (c) critically assess the efficacy of the community hub model in connecting learners with an educational pathway.